2004
DOI: 10.1113/jphysiol.2003.056812
|View full text |Cite
|
Sign up to set email alerts
|

Group II metabotropic glutamate receptors enhance NMDA receptor currents via a protein kinase C‐dependent mechanism in pyramidal neurones of rat prefrontal cortex

Abstract: The action of glutamate in CNS is mediated by the activation of metabotropic and ionotropic receptors. The metabotropic glutamate receptors (mGluRs) are highly enriched in prefrontal cortex (PFC) -a brain region critically involved in the regulation of cognition and emotion. Emerging evidence has suggested that mGluRs are viable drug targets for neuropsychiatric disorders associated with PFC dysfunction. However, the mGluR-mediated signalling in PFC remains unclear. To understand the physiological functions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 67 publications
7
65
0
Order By: Relevance
“…Pyramidal neurons located in the intermediate and deep layers (III-VI) of the rat PFC were recorded. Recordings of whole-cell ion channel currents used standard voltage-clamp techniques (Yan et al, 1999;Wang et al, 2003;Tyszkiewicz et al, 2004). The internal solution consisted of the following (in mM): 180 N-methyl-D-glucamine, 40 HEPES, 4 MgCl 2 , 0.1 BAPTA, 12 phosphocreatine, 3 Na 2 ATP, 0.5 Na 2 GTP, and 0.1 leupeptin, pH 7.2-7.3 (265-270 mOsm/l).…”
Section: Methodsmentioning
confidence: 99%
“…Pyramidal neurons located in the intermediate and deep layers (III-VI) of the rat PFC were recorded. Recordings of whole-cell ion channel currents used standard voltage-clamp techniques (Yan et al, 1999;Wang et al, 2003;Tyszkiewicz et al, 2004). The internal solution consisted of the following (in mM): 180 N-methyl-D-glucamine, 40 HEPES, 4 MgCl 2 , 0.1 BAPTA, 12 phosphocreatine, 3 Na 2 ATP, 0.5 Na 2 GTP, and 0.1 leupeptin, pH 7.2-7.3 (265-270 mOsm/l).…”
Section: Methodsmentioning
confidence: 99%
“…The first indication of the therapeutic potential of this drug came from animal models showing that mGlu2/3 agonist reduces the overactivity produced by NMDA antagonist [50,51]. Such reduction might occur as a result of presynaptic reduction in excitation, but a recent report raises the possibility of postsynaptic enhancement of the NMDAR function [52].…”
Section: Nmda Hypofunctionmentioning
confidence: 99%
“…We have recently reported that activation of group II mGluRs increases NMDAR currents in PFC pyramidal neurons via a PKC-dependent mechanism (Tyszkiewicz et al 2004). Considering that ␤-amyloid peptides impair the group I mGluR-mediated, PKC-dependent regulation of GABAergic transmission, we hypothesized that the group II mGluR-mediated, PKC-dependent regulation of NMDAR currents may also be impaired by A␤ exposure.…”
Section: ␤-Amyloid Peptides Impair the Group II Mglur-mediated Potentmentioning
confidence: 99%
“…For detecting activated PKC, a phospho-PKC (pan) antibody that recognizes PKC␣, ␤ I , ␤ II , ⑀, , and ␦ isoforms only when phosphorylated at a carboxyl-terminal residue homologous to Ser 660 of PKC␤ II was used in the Western blot analysis Tyszkiewicz et al 2004). After incubation, slices were transferred to boiling 1% SDS and homogenized immediately.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation